Desired Fertility and Children Born across Time and Space - Isabel Günther; Kenneth Harttgen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
With about five children born per woman and a population growth rate of 2.5 per cent per year, sub-Saharan Africa has been the world's fastest growing region over the last decade. Economists have often argued that high fertility rates are mainly driven by women's demand for children (and not by family planning efforts) with low levels of unwanted fertility across countries (and hence with little room for family planning efforts to reduce population growth). We study the relationship between wanted fertility and number of children born in a panel of 200 country-years controlling for country characteristics and global trends. In general, we find a close relationship between wanted and actual fertility, with one desired child leading to one additional birth. However, our results also indicate that in the last 20 years the level of unwanted births has stayed at two across sub-Saharan Africa whereas it has decreased from one to zero in other developing countries. Hence, women in African countries are less able to translate child preferences into birth outcomes than women in other developing countries, i.e. leaving plenty of room for family planning efforts; and forces other than fertility demand have been important for fertility declines in other developing countries. Family planning efforts only partly explain the observed temporal and spatial differences in achieving desired fertility levels.
Keywords: J10; J13; 330; Fertility; Population Growth; Development; Population Policies